IMPLEMENTASI PERILAKU KESEIMBANGAN HIDUP DI DUNIA DAN AKHIRAT PADA GENERASI MILENIAL - Darmawansyah, Taufik; Tartila Vazari; Suci Rahmadhani; Ardi Satrial (Program Studi Pendidikan Agama Islam, 2025)
The balance of life in the world and the hereafter is a behavior that must be applied in daily life. This study aims to explore the application of the balance between worldly and spiritual life by the millennial generation. In today's modern era, full of material orientation and practical lifestyles, many young people tend to ignore the religious dimension in their daily lives. This research uses a qualitative approach with descriptive methods to gain in-depth understanding through in-depth interviews, observations, and review of relevant literature to strengthen the data obtained. The findings show that some millennials are starting to build awareness to balance worldly achievements with spiritual responsibilities. This can be seen from participation in religious-social activities, time management between work and worship, and utilization of digital media to spread positive messages. This study suggests that fostering spiritual values should receive attention from families, educational institutions and the surrounding environment and strive to achieve a balance of worldly and afterlife life in the millennial generation. Awareness of the importance of the afterlife in living modern life is the foundation in creating a generation that is in harmony between the outer and inner aspects